THE USE OF TEXT ALOUD SOFTWARE IN TEACHING STUDENTS' PRONUNCIATION - Roslaini Roslaini; Cahya Komara (English Education Department, 2020)
Pronunciation is often viewed as difficult English sub-skill for EFL students in Indonesia. Many of students did not know how to respond the problem of pronunciation they have in class. Moreover, many teachers or lecturers also did not support the students’ pronunciation teaching and learning with a proper media. This situation happened in second semester students of English Department, FKIP UHAMKA Jakarta 2018/2019 Academic Year. In fact, there are plenty of technology applications that can support or assist them to practice pronunciation by their own. One of it is Text aloud Software. Thus, in this small-scale study, the researchers aim to reveal the use of Text Aloud Software as one of technology application that can help English as Foreign Language (EFL) students to mastery English pronunciation in the classroom. This study applies quantitative method with the use of quasi-experimental design and also added by close-ended questioners. The question of this research is; does Text Aloud Software help EFL students to master English pronunciation? To be able to answer the research question, this study involved 20 respondents who were selected purposively. The results showed that both data of pre-test and post-test in control class and experiment class was normally distributed and homogeny. The statistical test or t-test also showed that t observed (to = 1.68) was smaller than t table (tt = 2.02) which was 1.68 < 2.02. It can be concluded that Ho is rejected and Hi is accepted. Therefore, Text-Aloud Software is effective in helping students to master pronunciation.